(3x-6)(x-4)(x+6)=0

Simple and best practice solution for (3x-6)(x-4)(x+6)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-6)(x-4)(x+6)=0 equation:


Simplifying
(3x + -6)(x + -4)(x + 6) = 0

Reorder the terms:
(-6 + 3x)(x + -4)(x + 6) = 0

Reorder the terms:
(-6 + 3x)(-4 + x)(x + 6) = 0

Reorder the terms:
(-6 + 3x)(-4 + x)(6 + x) = 0

Multiply (-6 + 3x) * (-4 + x)
(-6(-4 + x) + 3x * (-4 + x))(6 + x) = 0
((-4 * -6 + x * -6) + 3x * (-4 + x))(6 + x) = 0
((24 + -6x) + 3x * (-4 + x))(6 + x) = 0
(24 + -6x + (-4 * 3x + x * 3x))(6 + x) = 0
(24 + -6x + (-12x + 3x2))(6 + x) = 0

Combine like terms: -6x + -12x = -18x
(24 + -18x + 3x2)(6 + x) = 0

Multiply (24 + -18x + 3x2) * (6 + x)
(24(6 + x) + -18x * (6 + x) + 3x2 * (6 + x)) = 0
((6 * 24 + x * 24) + -18x * (6 + x) + 3x2 * (6 + x)) = 0
((144 + 24x) + -18x * (6 + x) + 3x2 * (6 + x)) = 0
(144 + 24x + (6 * -18x + x * -18x) + 3x2 * (6 + x)) = 0
(144 + 24x + (-108x + -18x2) + 3x2 * (6 + x)) = 0
(144 + 24x + -108x + -18x2 + (6 * 3x2 + x * 3x2)) = 0
(144 + 24x + -108x + -18x2 + (18x2 + 3x3)) = 0

Combine like terms: 24x + -108x = -84x
(144 + -84x + -18x2 + 18x2 + 3x3) = 0

Combine like terms: -18x2 + 18x2 = 0
(144 + -84x + 0 + 3x3) = 0
(144 + -84x + 3x3) = 0

Solving
144 + -84x + 3x3 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3'.
3(48 + -28x + x3) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(48 + -28x + x3)' equal to zero and attempt to solve: Simplifying 48 + -28x + x3 = 0 Solving 48 + -28x + x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 24x-5+22x+5=180 | | 46x-5+5=180 | | 1000=(-1700)(10)+b | | 57/67×32/171×45/128 | | 5(x+3)-1(2x-7)= | | 13+4(x-5)=5-2x | | mx^2-(2m+1)x+(m-1)=0 | | 28x-2+110=180 | | -5(z+6)= | | 3(x+4)=6x-30 | | -5(2+6)= | | ax+5y+20=0 | | (8x+2)+(3x-2)=200 | | x+2=41562 | | (8x+2)+(3x+2)=200 | | 12b-4=36 | | 6X-5y-y= | | 2b-4-12b-9= | | 2x-4-16=0 | | 8h-h-7h= | | 5w+1w+6w= | | (X-3y+3)dx+(3x+y+9)dy=0 | | v^2/3-9v^1/3=-20 | | Lgx=1+3lgx | | 0.613=log(x) | | 6x+11+8x-7=180 | | x^2-60x+910=0 | | x^2-60x+190=0 | | 26+x=12 | | 2x-(4x-3/3)=1/2(3x-1) | | 48=6/y | | x(x-7)(x+13)=0 |

Equations solver categories